Globotriaosylceramide inhibits iNKT‐cell activation in a CD1d‐dependent manner. Issue 1 (20th October 2015) - Pereira, Catia S.; Sa‐Miranda, Clara; De Libero, Gennaro; Mori, Lucia; Macedo, Maria Fatima
Abstract : Globotriaosylceramide (Gb3) is a glycosphingolipid present in cellular membranes that progressively accumulates in Fabry disease. Invariant Natural Killer T (iNKT) cells are a population of lipid‐specific T cells that are phenotypically and functionally altered in Fabry disease. The mechanisms responsible for the iNKT‐cell alterations in Fabry disease are not well understood. Here, we analyzed the effect of Gb3 on CD1d‐mediated iNKT‐cell activation in vitro using human cells and in vivo in the mouse model. We found that Gb3 competes with endogenous and exogenous antigens for CD1d binding, thereby reducing the activation of iNKT cells. This effect was exerted by a reduction in the amount of stimulatory CD1d:α–GalCer complexes in the presence of Gb3 as demonstrated by using an mAb specific for the complex. We also found that administration of Gb3 delivered to the same APC as α‐GalCer, induces reduced iNKT‐cell activation in vivo. This work highlights the complexity of iNKT‐cell activation and the importance of nonantigenic glycosphingolipids in the modulation of this process.